Artificial Intelligence in Classroom Learning: Opportunities and Challenges for Developing Students’ Growth Mindset - Raden Rara Faiza Iflaal Ulima; Rahmatika Maulida; Yunus Mahben; Muhammad Ardi Kurniawan (The Indonesian Institute of Science and Technology Research, 2026)
The rapid development of Artificial Intelligence (AI) has transformed education, particularly in classroom learning. AI technologies, including intelligent tutoring systems, generative AI, and adaptive learning platforms, provide new opportunities to enhance learning experiences. However, their integration also raises important pedagogical questions regarding students’ critical thinking, autonomy, and growth mindset. This article examines how AI can function as both an opportunity and a challenge in fostering students’ growth mindset. The study employs a qualitative literature review by analyzing recent research on AI in education, critical thinking, and growth mindset. The findings indicate that AI improves access to information, supports personalized learning, and encourages reflective thinking. However, excessive dependence on AI may reduce deep cognitive engagement without appropriate pedagogical guidance. The discussion focuses on three key dimensions: AI as a learning support tool, a catalyst for critical thinking, and a factor influencing students’ confidence and autonomy. The findings emphasize the essential role of teachers in guiding students to use AI responsibly and reflectively. When effectively integrated into classroom activities, AI can promote inquiry, evaluation, and independent learning rather than replace human thinking. Therefore, AI should not be viewed simply as beneficial or harmful but as a pedagogical challenge requiring thoughtful instructional integration. This study concludes that, when supported by appropriate teaching strategies, AI can contribute positively to the development of growth mindset, critical thinking, and reflective learning, while reinforcing the importance of balancing technological innovation with sound educational practice.